Does outdoor education work equally for everyone? Examine influence of OEP on mental health and well-being in university students - Peng Wang; Mohd Yasim Mazuki (Environment and Social Psychology, 2025)
This study examines the relationship between outdoor education programs (OEPs) and mental health outcomes among Chinese university students, with a specific focus on demographic moderators. Adopting a quasi-experimental pretest-posttest control group design, 240 first-year undergraduates from Hengshui University were purposively sampled and assigned to either an experimental group (n=120) participating in a 5-day OEP or a waitlist control group (n=120). Data were collected using validated Mandarin versions of the GHQ-12 and GWB scales, and analyzed via paired t-tests, ANOVA, and independent samples t-tests to assess intervention effects and demographic influences. The results indicated three key outcomes: (1) The outdoor education program led to substantial improvements in positive emotions and self-confidence, reductions in negative emotions and stress. (2) Demographic factors significantly moderated mental health outcomes (χ²=3.258, F=9.819, p=0.002), yet no statistically significant effects were observed on well-being (χ²=1.709, F=1.578, p=0.210). (3) Treatment effects varied significantly across gender, age, academic discipline, and place of residence (p < 0.05), while prior outdoor experience and household income showed no moderating effects on mental health or well-being; The results contribute to theoretical frameworks by demonstrating the moderating effects of demographic variables on OEP efficacy, aligning with social cognitive theory and cultural adaptation models. Practically, these findings advocate for the development of demographic-specific OEPs to address differential needs, particularly among female students, physical education majors, and urban residents.